1997
DOI: 10.1172/jci119551
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of constitutive nitric oxide synthase (NOS) by nitric oxide generated by inducible NOS after lipopolysaccharide administration provokes renal dysfunction in rats.

Abstract: Excess NO generation plays a major role in the hypotension and systemic vasodilatation characteristic of sepsis. Yet the kidney response to sepsis is characterized by vasoconstriction resulting in renal dysfunction. We have examined the roles of inducible nitric oxide synthase (iNOS) and endothelial NOS (eNOS) on the renal effects of lipopolysaccharide administration by comparing the effects of specific iNOS inhibition, L -N 6 -(1-iminoethyl)lysine (L-NIL), and 2,4-diamino-6-hydroxy-pyrimidine vs. nonspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
169
2
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(194 citation statements)
references
References 37 publications
18
169
2
5
Order By: Relevance
“…Studies of the effect of the endotoxin lipopolysaccharide on the GI tract have associated delay in gastric emptying and intestinal transit with increased expression of inducible NOS (iNOS) (Takakura et al, 1997;Fan et al, 2001;De Winter et al, 2002). The substantial concentrations of NO which can be generated by iNOS are known to autoinhibit the constitutive forms of NOS (cNOS), which may result in a condition in which iNOS is overexpressed, while cNOS is concurrently inhibited (Schwartz et al, 1997). In mice, Fleming et al demonstrated that ethanol exposure upregulates the basal gene expression of iNOS in the ileum (Fleming et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effect of the endotoxin lipopolysaccharide on the GI tract have associated delay in gastric emptying and intestinal transit with increased expression of inducible NOS (iNOS) (Takakura et al, 1997;Fan et al, 2001;De Winter et al, 2002). The substantial concentrations of NO which can be generated by iNOS are known to autoinhibit the constitutive forms of NOS (cNOS), which may result in a condition in which iNOS is overexpressed, while cNOS is concurrently inhibited (Schwartz et al, 1997). In mice, Fleming et al demonstrated that ethanol exposure upregulates the basal gene expression of iNOS in the ileum (Fleming et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether other members of the AP-1 transcription factors play a role in the regulation of NOS3 expression in UAEC also needs to be investigated. Furthermore, the AP-1 family oncogene products can be rapidly induced by a variety of physiological and pathophysiological stimuli important for cell function, including hormones such as estrogen (Shiozawa et al, 2004), growth factors (Inoue et al, 1995;Zheng et al, 1999), shear stress (Li et al, 2003), protein kinase C activators (Navarro-Antolin et al, 2000), tumor necrosis factor-α (Hanazawa et al, 1994), lipopolysaccharide (Schwartz et al, 1997;Wong et al, 2004), and angiotensin II (Clark et al, 1992). In the uterine and placental circulations, the role of AP-1 in estrogen (Chen et al, 2006;Weiner et al, 1994) and angiogenic growth factors such as basic fibroblast growth factor (Zheng et al, 1999) as well as angiotensin II (Zheng et al, 2005) stimulation of endothelial NOS3 expression is currently unknown, which will be important to be investigated because of the key role(s) that these factors play in the regulation of uterine and placental vascular activity and reactivity during pregnancy.…”
Section: Disscussionmentioning
confidence: 99%
“…However, many studies have also demonstrated that the expression level of NOS3 gene can be up-regulated by many physiological and pathophysiological factors, including estrogen (Chen et al, 2006;Weiner et al, 1994;Zheng et al, 2005), growth factors (Inoue et al, 1995;Zheng et al, 1999), shear stress (Li et al, 2003), and protein kinase C activators (NavarroAntolin et al, 2000), whereas the inflammatory cytokines tumor necrosis factor-α (Yoshizumi et al, 1993) and bacterial toxin lipopolysaccharide (Schwartz et al, 1997) down-regulates the expression of this vasodilatory enzyme. The regulation of NOS3 expression in endothelial cells can take place at the levels of transcription (i.e., NOS3 promoter activity) and post-transcription (i.e., mRNA stability) (Fleming and Busse, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They have demonstrated that following similar L-NAME and L-NIL treatment, corresponding NOS isoforms were inhibited since LPS-induced hypotension was corrected. By the same manner, LPSinduced increase in both urinary excretion of nitrates-nitrites and cyclic GMP level was abolished (Schwartz et al, 1997;Lortie et al, 2000). Secondly, treatments had to be reversible since in this study we have investigated the role of NO as a trigger of the heat stress-induced cardioprotection and not as a mediator during the ischaemia-reperfusion sequence.…”
Section: Discussionmentioning
confidence: 96%
“…First, NOS isoforms had to be inhibited at the moment of heat stress. This point has been assessed by Schwartz et al (1997). They have demonstrated that following similar L-NAME and L-NIL treatment, corresponding NOS isoforms were inhibited since LPS-induced hypotension was corrected.…”
Section: Discussionmentioning
confidence: 99%